Neighborhood Meltdown: Small Soldiers - Collins, Terry (Landoll Inc, 1998)
Question:What happens when a military micro chip is implanted into the hottest new action figures? Answer: Neighborhood Meltdown.
Keywords: Juvenile literature-Fiction